Análise da priorização de atividades críticas em projetos lineares: estudo de casos em projetos ferroviários - Humberto Coelho de Melo (2014)
This thesis presents a exploratory study about the activities in conceptual engineering projects for linear projects (or infrastructure projects), specially railways, into the second phase of the methodology Front-End-Loading. Based on the analysis of four different railways, using the multiple case studies, it aimed to identify what activities of engineering could be prioritized considering its impact into the construction costs, into the construction planning and into the conceptual design planning. A survey was conducted to experts using the Delphi methodology to identify what are the most relevant activities to the scope definition in linear projects. From that exploratory research and from the survey, ten guidelines were suggested, of which we mention the Guideline 3: There are disciplines more relevant, which might be further developed, while the less relevant disciplines might be included into the budget as index from other similar projects, the Guideline 5: The disciplines of projects with similar nature and characteristics of the cases 1, 2 and 3 tend to be grouped by relevance as the following: Group 1 (Highest relevance): Preliminary studies of alignments, Topography, Geotechnical and Geological studies for conceptual projects (FEL-2), Infrastructure, Trade-offs, Geometric design and Earthwork. Group 2 (Medium/High relevance): Bridges, Tunnels, Superstructure and Geological and geotechnical plan for the next phase (basic design FEL-3). Group 3 (Medium relevance): Hydrology, Land acquisition, General characterization of the area to be studied, Interferences, Borrow material areas, Areas for material disposal. Group 4 (Medium/Low relevance): Building and facilities, Road access for maintenance, Construction site and Telecommunication and automation. Group 5 (Low relevance): Preliminary services and Landscaping and complementary services, and the Guideline 7: Suggest the analysis of the level of maturity of the conceptual projects in the end of FEL-2 consider the adherence of the products of engineering to the baseline focusing the resources available and efforts to the disciplines with the highest relevance. The study conclude that for railway projects with similar characteristics to the cases 1, 2 and 3, the most critical ones are Alignment analysis and definition of directions, Topography survey, Geological and geotechnical studies for conceptual projects in FEL-2, Infrastructure, Studies and definition of technical solutions (Trade-offs), Geometric design and Earthwork. On the other hand the research showed the importance of, in the beginning of each project, to identify the disciplines and the technical and management activities which will receive most part of resources and efforts to gain more maturity of the engineering products in the end of FEL-2 phase. This will may afford the increase of assertiveness and predictability of projects and, consequently, it will may contribute to improve the decision making process about go or dont go for these enterprises.